Post-Correctional Legal Implementation for Former Terrorism Convicts from a Justice Perspective - Vinanda Ade Pratama; Zakhroh Aulia Dewi (Ilomata International Journal of Social Science, 2026)
This study examines the legal construction of post-correctional punishment execution for former terrorism convicts within the Indonesian correctional system, focusing on the balance between security, reintegration, and justice after release. Existing scholarship generally emphasizes three perspectives: surveillance and risk management, deradicalization as a counterterrorism strategy, and limited rights-based reintegration analyses that inadequately address legal guarantees for former convicts. This study critically assesses the normative coherence of post-correctional legal frameworks in reflecting principles of justice, using Banyumas Regency as a contextual legal reference. A normative juridical method with qualitative analysis was employed, relying on statutory regulations, legal doctrines, and theories of justice concerning corrections, counterterrorism, and human rights. The analysis was conducted through statutory interpretation and doctrinal evaluation without empirical field investigation. The findings indicate that, although post-correctional supervision and deradicalization are formally regulated, the legal framework lacks detailed operational standards, measurable indicators, and effective coordination mechanisms at the local level. These normative gaps may hinder substantive justice by limiting proportional supervision and protection of former convicts’ socio-economic rights. The study concludes that the current framework has not fully incorporated restorative and reintegrative justice principles in a coherent and operational manner. Accordingly, a more structured, rights-oriented post-correctional model is required to strengthen legal certainty, community participation, social empowerment, and a balanced relationship between public security and individual rights protection.